Effect of increased concentrations of atmospheric carbon dioxide on the global threat of zinc deficiency: a modelling study. Issue 10 (October 2015) - Myers, Samuel S; Wessells, K Ryan; Kloog, Itai; Zanobetti, Antonella; Schwartz, Joel
Summary: Background: Increasing concentrations of atmospheric carbon dioxide (CO2 ) lower the content of zinc and other nutrients in important food crops. Zinc deficiency is currently responsible for large burdens of disease globally, and the populations who are at highest risk of zinc deficiency also receive most of their dietary zinc from crops. By modelling dietary intake of bioavailable zinc for the populations of 188 countries under both an ambient CO2 and elevated CO2 scenario, we sought to estimate the effect of anthropogenic CO2 emissions on the global risk of zinc deficiency. Methods: We estimated per capita per day bioavailable intake of zinc for the populations of 188 countries at ambient CO2 concentrations (375–384 ppm) using food balance sheet data for 2003–07 from the Food and Agriculture Organization. We then used previously published data from free air CO2 enrichment and open-top chamber experiments to model zinc intake at elevated CO2 concentrations (550 ppm, which is the concentration expected by 2050). Estimates developed by the International Zinc Nutrition Consultative Group were used for country-specific theoretical mean daily per-capita physiological requirements for zinc. Finally, we used these data on zinc bioavailability and population-weighted estimated average zinc requirements to estimate the risk of inadequate zinc intake among the populations of the different nations under the two scenarios (ambient and elevated CO2 ). The difference between the population at risk at elevated and ambient CO2 concentrations (ie, population at new risk of zinc deficiency) was our measure of impact. Findings: The total number of people estimated to be placed at new risk of zinc deficiency by 2050 was 138 million (95% CI 120–156). The people likely to be most affected live in Africa and South Asia, with nearly 48 million (32–63) residing in India alone. Global maps of increased risk show significant heterogeneity. Interpretation: Our results indicate that one heretofore unquantified human health effect associated with anthropogenic CO2 emissions will be a significant increase in the human population at risk of zinc deficiency. Our country-specific findings can be used to help guide interventions aimed at reducing this vulnerability. Funding: Bill & Melinda Gates Foundation, Winslow Foundation .